Polarography of Selenium and Tellurium: A New Arena of Electrochemistry - Sahu, G.P.; Lavale, S.C. (Asian Journal of Chemistry, 2010)
Investigations on polarographic behaviour and brief surveys of electrode kinetics of selenium and tellurium opened new arenas in electrochemical problems of importance. The polarogram of 1 mM Se(IV) was recorded under distinct experimental conditions. It produced single four-electron reduction wave in pH ranging trom 3 to 8 in NH4Cl as base electrolyte. At pH 4.2, Er½ value was found to be –1.522 V vs. SCE. Te(IV) undergoes reduction to its elemental state at pH 8.4. It gives ill defined wave at pH ≤8.0 Er½ value was found to be -0.684 V vs SCE. Er½ values were computed by Koutecky's method. The stepwise reduction +4, +2, 0, –2 was also observed on the polarograpic wave. The reduction states of the various waves of Se(IV) and Te(IV) observed have been established conclusively by the Devries and Kroon's millicoulmetric method. The striking feature of the polarogram of Te(IV) is the large maximum which appears at limiting current plateau. This may be due to polytellurite ion Te2–x on the electrode surface. Calibration plots, polarograms, kinetic parameters and each of the voltammetric data will be fruitful for analytical, clinical, alloy production and for industrial purposes.